HvRNASET2 Regulate Connective Tissue and Collagen I Remodeling During Wound Healing Process - Baranzini, Nicolò; Pulze, Laura; Tettamanti, Gianluca; Acquati, Francesco; Grimaldi, Annalisa (Frontiers in Physiology, 2021)
Several studies have recently demonstrated that the correct regeneration of damaged tissues and the maintaining of homeostasis after wounds or injuries is tightly connected to different biological events, involving immune response, fibroplasia and angiogenetic processes, in both vertebrates and invertebrates. In this context, our previous data demonstrated that the Hirudo verbana recombinant protein rHvRNASET2 not only plays a pivotal role in innate immune modulation, but it is also able to activate resident fibroblasts leading to new collagen production, both in vivo and in vitro. Indeed, when injected in the leech body wall, which represents a consolidated invertebrate model for studying both immune response and tissue regeneration, HvRNASET2 induces macrophages recruitment, fibroplasia and synthesis of new collagen. Based on these evidences, we evaluate here the role of HvRNASET2 on muscle tissue regeneration and extracellular matrix remodelling in rHvRNASET2-injected wounded leeches, compared to PBS-injected wounded leeches used as control. The results presented here not only confirm our previews evidences, reporting that HvRNASET2 leads to an increased collagen production, but also show that an overexpression of this protein might influence the correct progress of muscle tissue regeneration process. Indeed Moreover, due to its inhibitory effect on vasculogenesis and angiogenesis, HvRNASET2 apparently interfere with the recruitment of the myoendothelial vessel-associated precursor cells that in turn are responsible for muscle regeneration during wound healing repair.